Visible and controllable RFID tags - Taylor, Alex; Villar, Nicolas (Proceedings of the 28th of the international conference extended abstracts on Human factors in computing systems, 2010)
Radio frequency identification (RFID) tags containing privacy-sensitive information are increasingly embedded into personal documents (e.g., passports and driver's licenses). The problem is that people are often unaware of the security and privacy risks associated with RFID, likely because the technology remains largely invisible and uncontrollable for the individual. To mitigate this problem, we developed a collection of novel yet simple and inexpensive alternative tag designs to make RFID visible and controllable. This video and demonstration illustrates these designs. For awareness, our tags provide visual, audible, or tactile feedback when in the range of an RFID reader. For control, people can allow or disallow access to the information on the tag by how they touch, orient, move, press, or illuminate the tag (for example, Figure 1 shows a tilt-sensitive RFID tag).